2018
DOI: 10.1155/2018/4742305
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Saireito, a Traditional Japanese Herbal Medicine, in Reducing Postoperative Edema after Acquired Ptosis Surgery: A Prospective Controlled Trial

Abstract: Background Persistent edema is a common complication after the surgical treatment of blepharoptosis; however, no objective methods have been established for evaluating or treating this condition. We focused on the Japanese herbal medicine, Saireito, and evaluated its efficacy in reducing postoperative edema. Methods This was a prospective, nonrandomized, and controlled study. We evaluated the incidence of postoperative edema in a Control group using a subjective patient-assessed visual analog scales (VASs) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Other miscellaneous supplements demonstrated beneficial effects in patients undergoing craniofacial surgery. Saireito pills, a combination of 12 medicinal herbs, reduced incidence of edema in blepharoplasty patients when given postoperatively 16 . Postoperative topical olive oil application in sinonasal surgery patients resulted in significantly less crusting, improved wound healing, and reduced self-reported pain scores compared with saline application 17 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Other miscellaneous supplements demonstrated beneficial effects in patients undergoing craniofacial surgery. Saireito pills, a combination of 12 medicinal herbs, reduced incidence of edema in blepharoplasty patients when given postoperatively 16 . Postoperative topical olive oil application in sinonasal surgery patients resulted in significantly less crusting, improved wound healing, and reduced self-reported pain scores compared with saline application 17 .…”
Section: Resultsmentioning
confidence: 98%
“…Saireito pills, a combination of 12 medicinal herbs, reduced incidence of edema in blepharoplasty patients when given postoperatively. 16 Postoperative topical olive oil application in sinonasal surgery patients resulted in significantly less crusting, improved wound healing, and reduced self-reported pain scores compared with saline application. 17 Preoperative use of yunnan baiyao capsules for bimaxillary orthognathic surgery patients resulted in a significant reduction in intraoperative blood loss compared with the placebo group.…”
Section: Beneficial Healing Effectsmentioning
confidence: 97%
“…30 Previous investigations have reported that Shosaikoto has potential application as an anti-inflammatory drug by inhibiting proinflammatory cytokines and promoting endogenous enhancement of steroid secretion. 18,31 Therefore, Saireito has both antiinflammatory and water utilization benefits.…”
Section: Byakujutsu Saireitomentioning
confidence: 99%
“…17 Saireito is a combination of Goreisan and Shosaikoto and has both the hydragogue effect of Goreisan and the anti-inflammatory action of Shosaikoto. 18 Some case series and retrospective studies have shown that Goreisan and Saireito reduced the postoperative recurrence of CSDH. 14,15,19,20 Recently, 3 prospective and randomized studies have been conducted to investigate whether Goreisan reduces the recurrence rate of CSDH.…”
mentioning
confidence: 99%
“…Saireito has been used in the treatment of chronic kidney disease, diarrhea, acute gastritis, and various edematous disorders, such as subdural hematoma, chronic lymphedema, cirrhosis, and general edema. Saireito has also widely been used to treat various inflammatory diseases, such as rheumatoid arthritis [ 6 , 7 ]. Recently, herbal medications have been attracting attention for their effectiveness in circulatory disease; however, the association between the use of herbal medication and pleural effusion has not been well documented.…”
Section: Introductionmentioning
confidence: 99%